Transoesophageal cross-sectional echocardiography with a phased array transducer system. Technique and initial clinical results. Issue 1 (July 1982) - Schlüter, M; Langenstein, B A; Polster, J; Kremer, P; Souquet, J; Engel, S; Hanrath, P
Abstract : Cardiac imaging by transthoracic two dimensional echocardiography is impaired in patients with chronic lung disease, those with obesity, and those with abnormal chest wall configuration. In order to overcome these limitations, a miniature phased array ultrasound transducer fitted to the tip of a commercially available gastroscope was developed. Transducer position and orientation can be adjusted completely by external control of vertical displacement inside the oesophagus, rotation, and angulation. Introduction and operation of the transducer gastroscope system are usually well tolerated by the patients, since no mechanical vibrations are generated and there is no need for an oil bag to secure oesophageal wall contact. Cardiac images of high quality are obtained even from structures and regions that are poorly or not at all imaged from external transducer positions.